Bottom-up excited state dynamics of two cinnamate-based sunscreen filter molecules. Issue 40 (3rd October 2016) - Peperstraete, Yoann; Staniforth, Michael; Baker, Lewis A.; Rodrigues, Natércia D. N.; Cole-Filipiak, Neil C.; Quan, Wen-Dong; Stavros, Vasilios G.
Abstract : We have used time-resolved pump–probe spectroscopy to explore E -MMC's and E -EHMC's excited state dynamics upon UV-B photoexcitation. Abstract : Methyl- E -4-methoxycinnamate ( E -MMC) is a model chromophore of the commonly used commercial sunscreen agent, 2-ethylhexyl- E -4-methoxycinnamate ( E -EHMC). In an effort to garner a molecular-level understanding of the photoprotection mechanisms in operation with E -EHMC, we have used time-resolved pump–probe spectroscopy to explore E -MMC's and E -EHMC's excited state dynamics upon UV-B photoexcitation to the S1 (1 1 ππ*) state in both the gas- and solution-phase. In the gas-phase, our studies suggest that the excited state dynamics are driven by non-radiative decay from the 1 1 ππ* to the S3 (1 1 nπ*) state, followed by de-excitation from the 1 1 nπ* to the ground electronic state (S0 ). Using both a non-polar-aprotic solvent, cyclohexane, and a polar-protic solvent, methanol, we investigated E -MMC and E -EHMC's photochemistry in a more realistic, 'closer-to-shelf' environment. A stark change to the excited state dynamics in the gas-phase is observed in the solution-phase suggesting that the dynamics are now driven by efficient E / Z isomerisation from the initially photoexcited 1 1 ππ* state to S0 .